Unraveling the link between environmental factors and organizational improvisation - Arshad, Darwina; Abu Bakar, Lily Julienti; Ahmad, Hartini; Hassan, Saifulhafizi (2015)
Improvisation is currently considered to be novel in the business activity.Due to limited study on improvisation in Malaysian businesses, this paper aims to investigate the influence of environmental factors towards the organizational improvisation. Specifically, organizational resources which include tangible and intangible resources as well as the external environmental factors in which comprise of market and technological turbulence and competitive intensity are the factors determined to influence organizational improvisation.By examining 106 small medium-sized enterprises (SMEs) in northern region Malaysia, we found that internal and external environmental factors were able to influence the organizational improvisation.This finding outlines that the SME entrepreneurs should highlight the substantial effect of external and internal factors which are able to influence the spontaneity and creativity in decision making and execution process in sustaining the firm performance.Theoretically and in practice, this study on improvisation in the business represents potentially rich addition to the vocabulary of entrepreneurial decisions and actions.